2019
DOI: 10.1097/rli.0000000000000597
|View full text |Cite
|
Sign up to set email alerts
|

Breast Magnetic Resonance Spectroscopy at 3 T in Biopsy-Proven Breast Cancers

Abstract: Objectives: The role of functional techniques, such as magnetic resonance spectroscopy ( 1 H-MRS), as noninvasive tools to increase breast MR imaging reliability has been widely investigated during the last 2 decades. Considering the growing interest in tumor biology and its influence on functional parameters, the aim of this study was to investigate the relationship between 1 H-MRS parameters and breast cancer biomarkers and to evaluate whether the results of 1 H-MRS at 3 T can correlate with established brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Nowadays, a basic mpMRI protocol includes unenhanced sequences (T2 weighted and DWI) followed by the series of pre-and post-contrast T1-weighted acquisitions [13], since it was demonstrated that mpMRI including contrast-enhanced sequences and DWI increases diagnostic accuracy in BC diagnosis [16,24]. Also, magnetic resonance spectroscopy improves the diagnostic accuracy of breast MRI [25][26][27][28][29]; however, technical challenges and operator dependency have limited large-scale implementation of this technique [30].…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, a basic mpMRI protocol includes unenhanced sequences (T2 weighted and DWI) followed by the series of pre-and post-contrast T1-weighted acquisitions [13], since it was demonstrated that mpMRI including contrast-enhanced sequences and DWI increases diagnostic accuracy in BC diagnosis [16,24]. Also, magnetic resonance spectroscopy improves the diagnostic accuracy of breast MRI [25][26][27][28][29]; however, technical challenges and operator dependency have limited large-scale implementation of this technique [30].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, 16S rDNA could be used as a characteristic nucleic acid sequence for revealing biological species, which was considered to be the most suitable index for bacterial phylogeny and classification identification [12]. As early as 2005, Lenkinski et al [13] incubated the stool sample extract, and found that the intestinal flora of premenopausal breast cancer patients was significantly different from that of normal women, the number of Escherichia coli, A. aerobicus, Lactobacilli and non-fermenting bacteria increased significantly. With the development of gene sequencing technology, the research on intestinal flora has entered a new stage.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that MRS improves the diagnostic accuracy of breast MRI and the association between the detection of elevated total choline (tCho) levels and biological aggressive cancer phenotypes has been described [25,26,28,41]. In addition to tCho, in recent years MRS has been used to detect and monitor other metabolites, such as lipid metabolites, since lipid metabolism alterations have been associated with cancer development.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%